Naphthenic acid fraction compounds, produced by the extraction of bitumen from oil sands, alter survival and behaviour of juvenile yellow perch (Perca flavescens) - Jessie S. Reynolds; Chris K. Elvidge; Ian J. Vander Meulen; Caleb T. Hasler; Richard A. Frank; John V. Headley; L. Mark Hewitt; Diane M. Orihel (Canadian Science Publishing, 2024)
We evaluated whether naphthenic acid fraction compounds (NAFCs) extracted from oil sand tailings adversely affect fish survival and behaviour. Following a before-after-control-impact design, we housed wild-caught juvenile yellow perch (Perca flavescens) in outdoor mesocosms to assess survival and behaviour under baseline conditions, then exposed fish to one of three treatments: negative control, 2 mg/L NAFC, or 15 mg/L NAFC. We performed behavioural assays (no-stimulus activity, food stimulus, and predator stimulus using a model bird) and assessed a comprehensive suite of endpoints (equilibrium losses, activity, shoaling, burst swimming, freezing, and space use). We found that exposure to 15 mg/L NAFCs substantially reduced fish survival and impaired fish equilibrium in all three behavioural tests. Furthermore, exposure to NAFCs impaired anti-predator behaviour: while the activity of control fish increased by two-fold in response to a predator stimulus, fish exposed to 2 or 15 mg/L NAFC did not change their activity levels after stimulation. No significant changes were observed in other behavioural endpoints. Overall, our findings suggest that a week-long exposure to NAFCs at concentrations commonly found in tailings ponds, constructed wetlands, and other mining-impacted waters may affect multiple facets of fish behaviour that could ultimately lead to reduced fitness in fish populations.